Badan HAM ASEAN dalarn Kajian Normatif Sistem Hukum Perlindungan HAM Sub-Regional Asia Tenggara - Heribertus Jaka Triyana, Heribertus Jaka Triyana (Pusham Universitas Negeri Medan, 2013)
This articre aims at analayzing its existence for efective and practical human rights advocacy and adjudication in order to reveal legal expectation for the southeast Asian people. Furthermore, with regard to its efficacies in terms of its mandates and its authority, close attention to its influential and extensive works at promotion, consolidation and recommendation to better approach on thematic human rights issues should be highlighted in order to reveal the aforementioned hopes. It then developes certain theories in international human rights law, such as the social function of law as well as principle of complementarity as frameworks of legal analysis to test whether AICHR contributes for realization of this new lope in the future. Key Words: AICHR, human rights